Safe passing critical criterion for drawn top-coal on rear conveyor and accurate control approach for drawing opening dimension - Donghui LI; Dongyin LI; Shen WANG; Zhizeng HUANG; Qing LIU; Xueliang ZHANG; Lijun ZHENG; Xuhe ZHANG; Shiting ZHU (Meitan kexue jishu, 2023)
Fully mechanized top coal caving technology has become the mainstream way of high yield and high efficiency mining in extra thick coal seams in China. The accurate control of the top-coal drawing mechanical parts is of significance to realize the automation and intellectualization of top-coal caving mining. Mastering the spatial motion law of the coal caving mechanism is the premise of accurate control. The immediate shape of the hydraulic support coal caving mechanism is jointly controlled by the support height, support attitude, extension length of the plug plate, and the relative position of the rear scraper, which has an important impact on the coal caving opening and the coal-passing height of the support. This study establishes a 3–D numerical model of four- legs top-coal caving hydraulic support (No. ZF15000/27.5/42) by using the finite element software ABAQUS. Hinge and translator connectors are used to simulate the rotation behavior and expansion-contraction behavior for hinge point and plug plate, respectively. Taking the support height (H), tail beam swing angle (α), and the plug plate extension length (l) as control variables, the spatial motion law of the hinge point between shield beam and tail beam and the end of the plug plate are modeled. The critical security equation for evaluating collision between top-coal drawing mechanical parts and rear scraper is obtained by using Levenberg-Marquardt fitting iteration method. A database for describe the calibration relationship, which contains the end coordination of plug plate, the dimension of the top-coal drawing opening, and H, α, and l, is established. The sensor type and installation position for sensing and controlling the attitude of the top-coal drawing mechanism are recommended, the approach for calculating the tail beam angle based on travel sensor is derived. Through field verification of top-coal drawing opening width, it is concluded that the relative error between measured value and calculated value meets the requirements for accurate control of top-coal drawing mechanism. The approach for controlling the top-coal drawing opening dimension is proposed, which has been successfully applied in the field.